Estudo epidemiológico molecular da resistência a carbapenêmicos e fluorquinolonas e sua associação com sistema de secreção tipo III em Pseudomonas aeruginosa - Ferreira, Melina Lorraine (2014)
Introduction: Has been observed the global spread of different variants of P. aeruginosa that is often associated with increased virulence or the emergence of new antimicrobial resistance genotypes. There are few studies describing the association of the Type III Secretion System (TTSS) with antibiotic resistance and outcome of patients with pneumonia and bacteremia. Objectives: Determine the relation among resistance to carbapenems and fluoroquinolones and the Type III Secretion System (TTSS) effector genotype and its association with the poor prognostic in patients with ventilator-associated pneumonia (VAP) and bacteremia, identify mutations in the Quinolone Resistance Determining Regions (QRDRs), Metallo-β-Lactamase genes (MβL), virulence genes (algD, lasB e toxA) and clonal spread of isolates producing MβL. Material and Methods: A retrospective cohort was conducted to determine the risk factors for 30-day mortality in patients with the first episode of bacteremia (157 patients) and VAP (60 patients) caused by P. aeruginosa. Genes blaIMP, blaVIM, blaSIM, blaGIM and blaSPM, TTSS genes (exoT, exoS, exoY, exoU ) and virulence genes (lasB, algD, toxA) were detected by PCR; the sequencing was conducted for QRDR genes (gyrA e parC) on fluoroquinolone-resistant strains and the Pulsed-Field Gel Electrophoresis (PFGE) for molecular typing of positive strains for the MβL genes Results: The multivariate analysis showed that predictors independently associated with death in patients with bacteremia were inappropriate therapy and cancer. Carbapenem resistance was more frequent among strains of VAP (53.3%), however with the detection of MβL genes in one isolate (blaIMP), unlike blood, where the frequency of these genes was 16.1%, being 10.7% blaSPM genotype and 5.4% blaVIM genotype. The exoS gene was found in all blood and lung isolates and the exoU gene only in 9.4%. Substitution of threonine to isoleucine at position 83 in gyrA was the most frequent mutation among fluoroquinolone-resistant strains. It was detected a mutation at position 91 in parC gene (Glu91Lys) associated with mutation in gyrA (Thre83Ile) in a strain of extensively drug-resistant P. aeruginosa, exoT+exoS+exoU+ genotype, isolate from lung, not described in Brazil yet. Among the strains that harboring the TTSS virulence genes it was observed high resistance to gentamicin (93.7%) and low for amikacin (37.5%). The evaluation of the clonal relationship between isolates producing blaSPM, blaVIM and blaIMP genes showed similarity (more than 80%) among the blaSPM strains, which was not observed for those producing blaVIM gene. Conclusions: Our results confirm previous findings regarding the spread of blaSPM clone, with indirect evidence of its cross-spread in our hospital and polyclonal those containing the blaVIM gene. Inappropriate therapy is significant factor for poor prognosis among patients with bacteremia caused by multidrug-resistant P. aeruginosa , independent of the virulence TTSS genotype associated.